Obstetric complications of placenta previa percreta - Sparić, Radmila; Mirković, Ljiljana; Ravilić, Uroš; Janjić, Tijana (Vojnosanitetski pregled, 2014)
Introduction. Placenta previa is related to severe maternal and fetal morbidity. The increasing incidence of cesarean delivery rate causes a marked increase in abnormally invasive placenta over the past decades. The abnormally invasive placenta is becoming the foremost cause of obstetric hemorrhage and postpartum hysterectomy, causing a significant maternal and fetal morbidity and even mortality. Maternal morbidity in such cases also comprise politransfusion, development of disseminated intravascular coagulation, uterine rupture, cystostomy, fistula formation, ureteral stricture, intensive care unit admission, infection, and prolonged hospitalization, adult respiratory distress syndrome, renal failure, septicemia and even death. Case report. A 38-year-old gravida 3, para 2, was admitted to our hospital at 27 weeks of gestation as an emergency due to vaginal bleeding, previously diagnosed with an anterior placenta previa. Following tocolytic therapy, bleeding stopped. The patient was informed on the diagnosis and the possibility of life-threatening hemorrhage necessitating preterm delivery. She was given corticosteroids to enhance fetal lung maturity. At 28 weeks of gestation, she experienced massive vaginal bleeding, and a decision was made to perform emergency cesarean section. We made a corporeal transverse uterine incision well above the uterovesical fold and tortuous vessels, at the same time avoiding the superior edge of the placenta. The placenta was found to be densely adherent to the lower uterine segment, penetrating through it and infiltrating the posterior wall of the urinary bladder. An attempt to remove the placenta resulted in injury to the bladder wall and the uterine rupture at a previous cesarean scar. The decision was made to perform total abdominal hysterectomy with placenta left in situ. At present, both mother and the baby are well. Conclusion. Anticipation and the surgeon's judgment are leading factors for surgery, from the choice of uterine incision type to the decision to proceeding to hysterectomy in order to reduce maternal morbidity.
Keywords: placenta previa; risk assessment; cesarean section; hysterectomy; treatment outcome